Evaluation of the Implementation of the Covid-19 Vaccination Policy by the East Kutai Regency Health Office - Chika Putri Aprilia; Tri Sulistyaningsih (Universitas Muhammadiyah Gorontalo, 2022)
This study aims to study and evaluate the implementation of the Covid-19 Vaccination policy in Sanggata Utara District, as an effort to overcome the spread of the Covid-19 virus, by using previous research as a reference source, which is then analyzed to find out the urgency and differences between previous research and research conducted by the author. In addition, the researcher also compares with the results of the researcher's observations, so that it can make it easier for the author to understand the phenomena and problems that are occurring in the implementation of the Covid-19 Vaccination policy, so that a common thread can be drawn and analyzed more specifically about the role of the East Kutai Regency Health Office, as one of the stakeholders who play an important role in the implementation of the Covid-19 Vaccination policy. The author hopes that this research will provide problem-solving references for future use. This research is qualitative and uses a descriptive approach. This research also refers to the evaluation theory from Nurcholis so that through these methods and theories, it can be known that the results of this study found that the implementation of the Covid-19 vaccination program in Sangatta Utara District is quite optimal because it is in accordance with the technical guidelines for the implementation of vaccination, it's just that it is still lacking in terms of socialization to the community. The suggestion in this study is that in the future the East Kutai Regency Health Office will be more active in providing socialization to the community and improving the quality of work of implementers of the Covid-19 vaccination policy so that it can increase public interest in the Covid-19 vaccination.